Health-related quality of life and a cost-utility simulation of adults in the UK with osteogenesis imperfecta, X-linked hypophosphatemia and fibrous dysplasia. Issue 1 (December 2016) - Forestier-Zhang, Lydia; Watts, Laura; Turner, Alison; Teare, Harriet; Kaye, Jane; Barrett, Joe; Cooper, Cyrus; Eastell, Richard; Wordsworth, Paul; Javaid, Muhammad; Pinedo-Villanueva, Rafael
Abstract Background Health-related quality of life of adults with osteogenesis imperfecta (OI), fibrous dysplasia (FD) and X-linked hypophosphatemia (XLH) remains poorly described. The aim of this study was to describe the HRQoL of adults with osteogenesis imperfecta, fibrous dysplasia and X-linked hypophophataemia and perform a cost-utility simulation to calculate the maximum cost that a health care system would be willing to pay for a hypothetical treatment of a rare bone disease. Results Participants completed the EQ-5D-5 L questionnaire between September 2014 and March 2016. For the economic simulation, we considered a hypothetical treatment that would be applied to OI participants in the lower tertile of the health utility score. A total of 109 study participants fully completed the EQ-5D-5 L questionnaire (response rate 63%). Pain/discomfort was the most problematic domain for participants with all three diseases (FD 31%, XLH 25%, OI 16%). The economic simulation identified an expected treatment impact of +2.5 QALYs gained per person during the 10-year period, which led to a willing to pay of £14, 355 annually for a health care system willing to pay up to £50, 000 for each additional QALY gained by an intervention. Conclusions This is the first study to quantitatively measure and compare the HRQoL of adults with OI, FD and XLH and the first to use such data to conduct an economic simulation leading to healthcare system willingness-to-pay estimates for treatment of musculoskeletal rare diseases at various cost-effectiveness thresholds.